2016
DOI: 10.1016/j.bpj.2015.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electroosmosis in the Permeation of Neutral Molecules: CymA and Cyclodextrin as an Example

Abstract: To quantify the flow of small uncharged molecules into and across nanopores, one often uses ion currents. The respective ion-current fluctuations caused by the presence of the analyte make it possible to draw some conclusions about the direction and magnitude of the analyte flow. However, often this flow appears to be asymmetric with respect to the applied voltage. As a possible reason for this asymmetry, we identified the electroosmotic flow (EOF), which is the water transport associated with ions driven by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
118
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(144 citation statements)
references
References 58 publications
13
118
1
8
Order By: Relevance
“…Our BLM data showed that EcChiP interacted strongly with long-chain chitooligosaccharides but not with maltooligosaccharides, implying that the channel was specific for chitooligosaccharide uptake. Strong interaction with the higher molecular weight substrates is also a characteristic of other sugar-specific channels, such as LamB (37,38,49), VhChiP (8,48), and CymA (50). Consistent with this is an earlier in vivo study that showed no growth of S. marcescens expressingthenullChiPmutantinthepresenceofchitooligosaccharides larger than chitotriose (26).…”
Section: Discussionmentioning
confidence: 58%
“…Our BLM data showed that EcChiP interacted strongly with long-chain chitooligosaccharides but not with maltooligosaccharides, implying that the channel was specific for chitooligosaccharide uptake. Strong interaction with the higher molecular weight substrates is also a characteristic of other sugar-specific channels, such as LamB (37,38,49), VhChiP (8,48), and CymA (50). Consistent with this is an earlier in vivo study that showed no growth of S. marcescens expressingthenullChiPmutantinthepresenceofchitooligosaccharides larger than chitotriose (26).…”
Section: Discussionmentioning
confidence: 58%
“…Thes ingle-channel measurement was carried out in the presence of 0.2 mm norfloxacin. In as imilar analysis we obtained the voltage-dependent association rate and dwell time (Figure 3) [18,20] Increasing negative voltages increases k on in OmpF wt from 1.3 10 4 to 1.8 10 5 m À1 s À1 in an exponential [a] flux at 1mm Arginine-Cl gradient was determined.…”
Section: Communicationsmentioning
confidence: 87%
“…Mit einer ähnlichen Analyse wie oben erhielten wir die spannungsabhängige Assoziationsrate und die Aufenthaltszeiten (Abbildung 3). [18,20] In OmpF wt führen steigende negative Spannungen zu einem exponentiellen Anstieg der Assoziationsrate von 1.3 10 4 auf 1.8 10 5 m À1 s À1 ,w ährend die Verweildauer 700 msa uf 60 msl inear abnimmt. Die OmpF E181C MTSES Mutante ergab einen ähnlichen Tr end bezüglich der Spannungsabhängigkeit der Assoziationsrate (5 10 3 bis 2.5 10 6 m À1 s À1 [a] Fluss umgerechnet auf 1mm Arginin-Cl-Gradient.…”
Section: Angewandte Chemieunclassified
“…[18,20] In OmpF wt führen steigende negative Spannungen zu einem exponentiellen Anstieg der Assoziationsrate von 1.3 10 4 auf 1.8 10 5 m À1 s À1 ,w ährend die Verweildauer 700 msa uf 60 msl inear abnimmt. Mit einer ähnlichen Analyse wie oben erhielten wir die spannungsabhängige Assoziationsrate und die Aufenthaltszeiten (Abbildung 3).…”
unclassified